The use of all-ceramic restorations to splint periodontally compromised teeth: A clinical report - KÖSE, KEMAL NACİ (MOSBY-ELSEVIER, 2005)
This clinical report describes the use of an all-ceramic system to restore periodontally compromised teeth. A metal-free post-and-core system and all-ceramic crowns were used to splint the teeth and fulfill the esthetic demands.